Economical, environmental and ethical impact of food wastage in hospitality and other global industries - Racz, Aleksandar (Array, 2018)
There is something horrible about throwing food in the bin. Based on existing literature, 30-50 percent (i.e. 1.2-2 billion tons) of the produced food never reaches anyone’s plate. Global food production can be split into production losses, consumers’ waste and consumption. In a world where 850 million people are undernourished, global food supply per person approximates to 570 kg: roughly, 380 kg is consumed, 140 kg is lost in the production and 50 kg is wasted by consumers. Households generate 53% of the total food waste in Europe, the processing industry 19%, food services 12%, the primary production sector 11%, and the retail/wholesale sector 5%. The European hospitality industry is a small food waster that generates only 12% of the total food waste in Europe. Wasted food is accountable for 3.3 GtCO2e. The average carbon footprint of food wastage is about 500 kg of CO2 equivalents per person per year. The blue water footprint of food wastage is about 250 km3. 1.4 billion Ha of land – 28% of the world’s agricultural area – is used annually to produce food that is either lost or wasted. The food which is not eaten contributes to the loss of biodiversity through habitat change, overexploitation, pollution and climate changes. Prompted in part by global food production inefficiency, 9.7 million hectares are deforested annually to grow food – 74% of the total annual deforestation. The scale of global food wastage is shocking, and this wasted food results in a number of ethically questionable implications. Pope Francis rightfully points out that from the moral standpoint prodigal expenditure and wasting of food is no better than stealing from the hungry and poor. From the ecological standpoint, it is no better than stealing from our own children.